Street life in renaissance Rome : A brief history with documents - Bell, Rudolph M (Boston Bedford/St. Martin's, 2013)
Highlighting daily life in Renaissance Rome, Street Life in Renaissance Rome uses both primary sources and illustrations to look at this era from the bottom up, focusing on the era's impact on ordinary citizens, the plight of social outcasts, and the dangers of urban life.
Includes bibliographies and index
Keywords: Tham khảo